2021
DOI: 10.37496/rbz5020200111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ensiling on the feeding value of flint corn grain for feedlot beef cattle: A meta-analysis

Abstract: The objective of this study was to review the effect of ensiling on the feeding value of flint corn grain and performance of feedlot cattle. In this meta-analysis, ensiled corn grain included both high-moisture corn and rehydrated corn grain. The criteria for a publication enter in the database were: diet was offered as a total mixed ration, diet contained at least 300 g/kg dry matter (DM) of ensiled or dry corn grain, and ensiled grain contained a minimum of 280 g/kg of moisture. The final dataset included 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…These results provided an increase of 13.3% in feed efficiency of animals fed rehydrated corn in replacement of dry corn. Similar to the results found in this trial, Jacovaci et al (2021) observed that the replacement of dry corn with rehydrated corn also did not affect the ADG, but there was a reduction in the DMI of 14.1% and an improvement in feed efficiency of 18.3%.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results provided an increase of 13.3% in feed efficiency of animals fed rehydrated corn in replacement of dry corn. Similar to the results found in this trial, Jacovaci et al (2021) observed that the replacement of dry corn with rehydrated corn also did not affect the ADG, but there was a reduction in the DMI of 14.1% and an improvement in feed efficiency of 18.3%.…”
Section: Discussionsupporting
confidence: 87%
“…In recent meta-analyses about the effect of ensiling on the feeding value of flint corn grain for feedlot beef cattle, Jacovaci et al (2021) found that the inclusion of ensiled corn in diets increased total tract digestibility of DM by 4.59% and starch by 3.33%, decreased DM intake by 14.1%, and increased feed efficiency by 18.3% but did not affect average daily gain (ADG). However, these benefits of grain ensiling are based on three major factors (Gomes et al, 2020): moisture content (Owens et al, 1997), particle size (Rémond et al, 2004), and length of storage time (Hoffman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The predominant cultivation of corn hybrids in Brazil, with a higher proportion of vitreous endosperm [9][10][11], is negatively related to starch digestibility [12][13][14], making ensiling an advantageous practice in terms of storage management and nutritive value [15][16][17]. In addition, ensiling reduces insect and rodent damage normally seen in dry grains and increases starch digestibility [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The consequence of this lack of structure for storing grains is the damage caused by rodents, insects and fungi (Mombach et al, 2019). rehydrated (reconstituted) Thus, corn grain silage has been used to circumvent these losses (C. M. Silva et al, 2016), and to improve the starch digestibility of corn (Ferraretto, Silva, Fernandes, Kim, & Sultana, 2018) and nutrient utilization by ruminants (Castro et al, 2019;Jacovaci, Salvo, Jobim, & Daniel, 2021). Furthermore, the technique of ensiling corn grain or another cereal makes it possible to purchase this ingredient at times with lower market costs, which is essential on farms and, especially, in the semi-arid region.…”
Section: Introductionmentioning
confidence: 99%